Beware of the existence of a big bath with asset impairment after pandemic covid-19! - Alwan Sri Kustono; Aisa Tri Agustini; Scherrgyo Agung Rhyo Dermawan (The Indonesian Accounting Review, 2021)
This study attempts to investigate the relationship between big bath accounting and asset impairment. It used the sample consisting of 231 firm-year observations from 33 mining companies listed on the Indonesia Stock Exchange during the 2012 to 2018 period. Logistic regression has been used to analyze a big bath accounting on assets impairment. The results provide evidence that companies that tend to do a big bath accounting will recognize a loss of asset value. A big bath accounting is done because managers assume that investors will respond when the company suffered large losses or small losses. The manager acknowledges the costs of future periods and current period losses when unfortunate unavoidable circumstances in the current period. It will consequently make a profit higher than expected in the next year. In the next period, the company’s performance will look better so that managers can maximize utility in the form of compensation for the targets that have been achieved.